Parasite-Modified Chemical Communication: Implications for Aquatic Community Dynamics - Friesen, Olwyn C.; Detwiler, Jillian T. (Frontiers in Ecology and Evolution, 2021)
Chemical communication within an aquatic environment creates an intricate signaling web that provides species with information about their surroundings. Signaling molecules, like oxylipins, mediate a multitude of interactions between free-living members of a community including non-consumptive effects by predators. Parasites are another source of signaling molecules in aquatic communities and contribute directly by synthesizing them or indirectly by manipulating host chemical cues. If chemical cues of infected hosts are altered, then non-consumptive interactions between other members of the community may also be affected. Different cues from infected hosts may alter behaviors in other individuals related to foraging, competition, and defense priming. Here, we discuss how parasites could modify host chemical cues, which may have far reaching consequences for other community members and the ecosystem. We discuss how the modification of signaling molecules by parasites may also represent a mechanism for parasite-modified behavior within some systems and provide a mechanism for non-consumptive effects of parasites. Further, we propose a host-parasite system that could be used to investigate some key, unanswered questions regarding the relationship between chemical cues, parasite-modified behavior, and non-consumptive effects. We explain how trematode-gastropod systems can be used to test whether there are alterations in the diversity and amounts of signaling molecules available, and if habitat use, immune function, and behavior of other individuals and species are affected. Finally, we argue that changes to pathway crosstalk by parasites within communities may have broad ecological implications.